BALANCE PROBLEMS OF INTERRELATIONS OF THE INSTITUTIONS OF THE NATIONAL INNOVATION SYSTEM OF THE RUSSIAN FEDERATION - Y. Danilina (Вестник университета)
The article reviews the problems preventing the formation of the integrated national innovation system of Russia. It has been concluded that most of these problems are related to the lack of a balance in cooperative links both between the institutions, components of national innovation system (NIS), and inside these institutions. The possibility of using the concept of the triple helix, based on the creation of a system of horizontal network interactions, was considered in the process of building the domestic NIS. The resources that the state expands on the imposition of standard actions to develop innovative competencies for the subjects of the innovation system was proposed to redirect on the institutionalization of independently emerging horizontal links between them, and on the analysis and dissemination of positive experience in establishing «innovative links» at all levels.